Ulcerative Lesions: A Rare Cutaneous Manifestation of Brucellosis - Abbas Azadi; Payman Jafarpour Fard; Mohammad Almasian (Case Reports in Medicine)
Brucellosis is a disease that is transmitted from animals to humans mainly via the consumption of unpasteurized dairy products, and it can involve any organ all over the body. Here, we report a significant rare case of brucellosis with cutaneous manifestations in a 52-year-old male patient whose disease was diagnosed via a serology test. The patient received standard antibiotic treatment, and his cutaneous lesions healed quickly. Although the cutaneous manifestations of brucellosis are exceedingly rare, in case of encountering ulcerative lesions and other cutaneous findings, particularly in endemic areas, infection with brucellosis should be kept in mind as an important differential diagnosis.